PENGARUH PENAMBAHAN DEDAK PADI DAN TEPUNG JAGUNG TERHADAP KUALITAS FISIK SILASE RUMPUT GAJAH (Pennisetum purpureumcv.Hawaii) - Kojo, Raldi M.; Rustandi, D.; Tulung, Y. R.L.; Malalantang, S. S. (ZOOTEC, 2015)
ABSTRACT EFFECT OF THE ADDITION OF RICE BRAN AND CORN FLOUR ON THE PHYSICAL QUALITY OF ENSILAGE ELEPHANT GRASS (Pennisetum purpureumcv.Hawaii). The purpose of this research was to determine the effect of the addition of rice bran and corn flour on the physical quality of elephant grass (Pennisetum purpureum cv. Hawaii)silage.The present study used elephant grass (Pennisetum purpureum cv. Hawaii)in the ensilage process. Rice bran and corn flour were then added to the elephant grass in the ensilage processing. The present study used Completely Randomized Design with 7 treatments and 5 replications. The treatments were formulated as follow: R0 = elephant grass 100%; R1 = elephant grass + 8% rice bran; R2 = elephant grass + 12% rice bran; R3 = elephant grass + 8% corn flour; R4 = elephant grass + 12% corn flour; R5 = elephant grass + 4% rice bran + 4% corn flour; R6 = elephantgrass + 6% rice bran + 6% corn flour. The variables measured were physical quality of elephant grass silage, including: Â texture, color, and aroma. The research results showed that the addition of rice bran and corn flour did not significantly affect (P>0,01) ensilage color and aroma, but significantly affect (P<0,01) the texture of the ensilage. It can be concluded that the addition ofÂ  8% rice bran gave the best result on theensilage textureof elephant grass (Pennisetum purpureum cv. Hawaii). Keywords : Elephant Grass, Ensilage, Rice Bran, Corn Flour, Physical Quality